2020
DOI: 10.1002/ps.6001
|View full text |Cite
|
Sign up to set email alerts
|

The role of mab‐3 in spermatogenesis and ontogenesis of pinewood nematode, Bursaphelenchus xylophilus

Abstract: Background: Bursaphelenchus xylophilus is one of the most destructive invasive species, causing extensive economic losses worldwide. The sex ratio of female to male of B. xylophilus plays an important role in the nematode infestation. However, little is known about the processes of its sex determination. The double sex/mab-3-related family of transcription factors are highly conserved in animals, playing crucial roles in sex determination, spermatogenesis and ontogenesis. We therefore investigated its ortholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…In recent years, the sex-determining genes of B. xylophilus have been extensively studied. For example, mab-3 is essential for spermatogenesis in B. xylophilus ( Zhou et al, 2020 ). In addition, more and more evidence indicates that the sex determination mechanism of B. xylophilus is also affected by environmental factors, such as nutrient conditions ( Wei et al, 2021 ) and volatile substances concentration ( Cui et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the sex-determining genes of B. xylophilus have been extensively studied. For example, mab-3 is essential for spermatogenesis in B. xylophilus ( Zhou et al, 2020 ). In addition, more and more evidence indicates that the sex determination mechanism of B. xylophilus is also affected by environmental factors, such as nutrient conditions ( Wei et al, 2021 ) and volatile substances concentration ( Cui et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under a microscope, a virgin male and virgin female were placed in a drop of water on a concave glass slide. In a humidifier, the slides were stored in the dark at 25°C ( Zhou et al, 2020 ). A zoom stereomicroscope (Zeiss, Thornwood, United States) was used to investigate the mating behavior of male and female adults.…”
Section: Methodsmentioning
confidence: 99%
“…When a large number of females were in an egg-bearing state, nematodes were separated and added to sterilized double-distilled water (ddH 2 O), and eggs were laid in an incubator set at 25°C for 1 h. The nematode suspension was gently removed and washed once or twice, and synchronized nematode embryos were obtained by adding ddH 2 O to the Petri dishes. Synchronized second-stage juvenile (J2) larvae were obtained by adding ddH 2 O to the synchronized embryos and placing them in an incubator at 25°C for 24 h. Synchronized third and fourth parasitic stage (J3 and J4) larvae and adults were obtained by culturing synchronized J2 larvae on gray mold plates and incubating them at 25°C for 36, 48, and 60 h, respectively ( Zhou et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…They discovered that the Bxy-fuca gene is primarily expressed in the body wall muscles and intestine. Subsequently, Zhou et al (2021) also successfully utilized whole-mount in situ hybridization for intact nematode using DIG-labeled single-stranded RNA (ss RNA) probes. Wen et al (2021) applied the DIG-labeled antisense cDNA probes and the whole-mount in situ hybridization to the intact pine wood nematode and demonstrated that BxSCD1 was specifically expressed in the dorsal glands and intestine of PWN.…”
Section: Introductionmentioning
confidence: 99%
“…B. xylophilus strain used in the current study was initially isolated from the wilted Pinus massoniana in China, and then raised on the mycelia of Botrytis cinerea (non-sporulating strain) grown on potato dextrose agar (PDA) Petri dishes at 25 °C. C. elegans N2 strain was raised on nematode growth medium Petri dishes inoculated with Escherichia coli OP50 strain at 20 °C 36 . Nematodes were extracted from the Petri dishes via Baermann funnel technique 37 .…”
Section: Methodsmentioning
confidence: 99%